Designation of a neotype for Parastacus nicoleti (Philippi, 1882) (Crustacea: Decapoda: Parastacidae) - Ribeiro, Felipe Bezerra; Araujo, Paula Beatriz (Zootaxa, 2017)
The type specimen of Parastacus nicoleti (Philippi, 1882) was not designated and the material used for the description has never been found. We designate herein the neotype of P. nicoleti based on the examination of specimens from the type locality deposited in the Museo Nacional de Historia Natural of Chile previously analyzed by Bahamonde (1958), who confirmed the identity and validated the species. To improve the species description we included new drawings and provide additional morphological characters. A synonym list and updated distribution map of this species are also provided.